A numerical and experimental study on the dynamical behavior of 3D-Panel Wall on Piloti RC Frame. Issue 4 (13th August 2018) - Kabir, Mohammad Zaman; Shadan, Parisa; Kabir, Hossein
Abstract : Purpose: The purpose of this paper is to examine the dynamical behavior of a combined three-story building with a 3D panel wall system including a soft story irregularity at the very first floor by doing a shaking table test. The upper two stories of the model were made out of the 3D panel system, while the first story was constructed only with moment-resisting RC frames. Design/methodology/approach: Besides the experimental program, the numerical finite element method was implemented for the verification of the experimental results. In the experimental study, the building responses including the floors' accelerations and drifts were considered, and the seismically vulnerable zones were reported and compared with that provided by the implemented FEM-based program. Findings: After the shaking table test, the major cracks appeared at the end of each column and beam-column connections. Some negligible cracks were also visible around the beam-panel connections. However, no crack was seen in the upper stories. The lateral deformation of the studied building was investigated under the applied ELC25 and NGH135 earthquakes. Under the both aforementioned ground motion records, the first story drift was larger than two upper stories, since the moment-resisting frame was a soft story. The hysteretic relation between the shear and displacement for each story was studied. Under the applied ELC25 earthquake, the system remains linear and the stiffness of each story is obtainable as well. Originality/value: This is the first time when the dynamical behavior of a combined system is studied and tested experimentally and numerically for data validation. Regarding the response of the assumed combined structure, the 3D panel system has a remarkable rigidity with respect to the conventional RC frames, also 3D panels have less weight than the moment-resisting frames.